Differences in Urine Protein Levels of Hemodialysis Patients With Acetic Acid and Lemon Juice Examination - Nurani Ai Erlinawati; Mamay Mamay; Nita Wahyuni (LPPM STIKes Muhammadiyah Ciamis, 2023)
Background and Objectives: Urine protein examination is a routine examination performed to determine kidney function. The principle of urine protein examination is that the protein in urine is denatured by heating and adding acid. Lemon fruit has a high acid content and lemon has similar properties to acetic acid, namely properties as a weak acid with a pH of 3.0. The direction of this research is to understand the comparison of urine protein using lemon juice and acetic acid solution reagents. Methods: This research uses experimental techniques because urine is treated directly by testing using a 6% acetic acid solution (control) and lemon juice solution. Results: the examination results using lemon juice solution are the same as the examination results using 6% acetic acid solution (control), using the Wilcoxon test, the Asymp.sig (2-tailed) value is 1.000. With the provisions of the test >0.05, Ho is accepted and Ha is rejected, so testing the difference in urine protein levels of hemodialysis patients with acetic acid and lemon juice examination can be carried out. Conclusion: The results of urine protein examination with acetic acid (control) and lemon juice as an alternative reagent. There is no difference in the results of urine protein examination using 6% acetic acid reagent and lemon juice.